2015
DOI: 10.1590/1809-4430-eng.agric.v35n6p998-1008/2015
|View full text |Cite
|
Sign up to set email alerts
|

Soil physical attributes in chemigated banana plantation with wastewater

Abstract: ABSTRACT:The feasibility of using sewage wastewater as a water and nutrient source for plants is an alternative to harness agricultural natural resource, observing its influence on the organic matter dynamics and soil energy. Our objective here was to evaluate the effects of applying different doses of effluent from a sewage treatment plant, in Janaúba -MG, Brazil, over the physical attributes of a soil grown with "Prata Anã" banana. From soil sample collection at depths of 0-20, 20-40, and 40-60 cm, we determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
(16 reference statements)
1
5
0
Order By: Relevance
“…It was not verified a significant effect of the water sources on the TOC level of the soil, probably due to the increase of the mineralization rate, due to the increase of the microbial activity, a fact favored by the high temperature of the region, corroborating with the results obtained by Marinho et al (2013), Andrade Filho et al (2013) and Alves et al (2015).…”
Section: /7supporting
confidence: 78%
“…It was not verified a significant effect of the water sources on the TOC level of the soil, probably due to the increase of the mineralization rate, due to the increase of the microbial activity, a fact favored by the high temperature of the region, corroborating with the results obtained by Marinho et al (2013), Andrade Filho et al (2013) and Alves et al (2015).…”
Section: /7supporting
confidence: 78%
“…According to and Alves et al (2015), in the soil total porosity and its subdivisions, the main interferences through handling wastewater would occur due to the suspended solids. Therefore, the relation with the highest values of macroporosity and lowest of microporosity obtained with the smaller doses of treated sewage effluent (TSE) are possibly related to the supply of organic substances that are part of TSE to the soil.…”
Section: Resultsmentioning
confidence: 99%
“…However, the increase of TSE doses and consequent elevation of supply to the total suspended solids (TSS), besides the increase in electrical conductivity (Tables 1 and 3), can be associated with a possible dispersed clay eluviation, causing pore clogging and consequent macroporosity reduction as shown in the treatments E 75% and E 100% for clay dispersion. Since macroporosity is essential for soil aeration and plant development, it can be concluded that high doses of TSE had a negative effect on soil quality (Alves et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…The use of wastewaters in banana crops alter soil organic matter and sodium contents (ALVES et al, 2015) and increases phosphorus, sulfur, total acidity, and base saturation levels in subsurface layers of irrigated soils (SANDRI; ROSA, 2017). These effects vary depending on the effluent composition, application management, and edaphic conditions.…”
Section: Introductionmentioning
confidence: 99%